Procedura dokonywania zmian w rejestrze zakładów żywnościowych - aspekty prawne - Sokołowski, Łukasz Mikołaj (Wydawnictwo Naukowe UAM, 2014)
The procedure of entering changes to the register of food companies – legal aspects S u m m a r y The aim of this paper was to resolve the doubts which arise in the process of ente ring changes to the register of food companies and, in particular, to answer the question of how information on modifications should be submitted to competent bodies, and the de lege ferenda postulates be presented. The current regulation as it is, may certainly seem to be inconsistent and internally contradictory. As such, it entails a number of practical problems, and those are encountered not by the approved and registered entities, but also by organs of administration and end-consumers whose life, health and fair interests should be given utmost legal protection. The currently biding and applicable legal state requires a change, or at least an adoption of such a practice by administrative organs, which will recognise an entry of a change to a register as an entry into a register, and in the case of the activity being modified, it will require an application filed, requesting an entry or an approval an entry in the register. However, it would be recommended and justified to enact legislation providing that an entry or a deletion of an entry (being struck out) also constitutes an entry to the register.

La procedura di denuncia delle modifiche al registro degli stabilimenti alimentari – aspetti giuridici R i a s s u n t o L’obiettivo dello studio è quello di chiarire i dubbi relativi a come apportare modifiche al registro degli stabilimenti alimentari, in particolare la questione di come comunicare all’autorità competente le informazioni riguardanti le modifiche, e di presentare le proposte de lege ferenda. L’attuale regolazione in materia di modifiche apportate al registro degli stabilimenti alimentari può sembrare incoerente e contraddittoria. Essa fa nascere molti problemi pratici non solo per gli stabilimenti riconosciuti e registrati, ma anche per gli enti amministrativi e i consumatori finali, la cui vita, salute e interessi commerciali dovrebbero essere protetti dalla legge con la massima cura. L’attuale situazione giuridica in questa materia necessita di essere cambiata oppure che venga adottata presso gli enti amministrativi la pratica di considerare le modifiche apportate al registro come iscrizione al registro, invece nel caso di trasformazione dell’attività che venga richiesta la presentazione della domanda di iscrizione oppure quella di riconoscimento e iscrizione al registro. Tuttavia sarebbe opportuno introdurre la regolazione che preveda che la modifica apportata all’iscrizione oppure la cancellazione della stessa costituiscano una iscrizione.